PENGARUH KECERDASAN EMOSIONAL GURU TERHADAP MOTIVASI DAN KEMAMPUAN BRPIKIR KRITIS SISWA DALAM MATA PELAJARAN IPS KELAS VII SMP MUALLIMIN WONODADI BLITAR - Rizqi Trisnaningtyas; Nur Isroatul Khusna (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of teachers’ emotional intelligence on students’ learning motivation and critical thinking skills in Social Studies for seventh-grade students at SMP Muallimin Wonodadi Blitar. A quantitative non-experimental causal-comparative design was employed, involving all 25 seventh-grade students as the sample. Data were collected using questionnaires, tests, and documentation, and analyzed through simple linear regression and correlation using SPSS 26. The results indicate that teachers’ emotional intelligence has a significant effect on students’ learning motivation, contributing 42.1%. In addition, learning motivation shows a strong and positive relationship with students’ critical thinking skills (r = 0.750; p < 0.05). These findings highlight the important role of teachers’ emotional intelligence in fostering students’ motivation and critical thinking abilities.